Drilling Processes with Hydraulic Percussion Rock Drills - Kimihiro HASHIBA; Katsunori FUKUI; Masahiro KOIZUMI (Journal of MMIJ, 2017)
Rock drills were developed about two hundred years ago, and hydraulic percussion rock drills are about half-century old. Performance and efficiency of rock drills have been increased by a number of researchers and engineers. Percussion energy was dramatically increased with changing the power source from pneumatic to hydraulic pressures; rods and rod joints were improved to endure the high percussion energy; carbide button bits were developed for hard rock drilling. This paper reviewed the previous studies and future issues on the drilling processes with hydraulic percussion rock drills. Studies on the stress wave propagation in rods and rod joints were based on theoretical and graphical methods and recently on numerical simulation. Studies on the interaction between a button bit and rock included crack propagation in rock, force-penetration relationship during drilling, and bit wear. Studies on the factors affecting drilling efficiency and drilling rate made a transition from simple to precise numerical simulations. Finally, important future issues were presented for the further progress of hydraulic percussion rock drills.